South Asian diets and insulin resistance - Misra, Anoop; Khurana, Lokesh; Isharwal, Sumit; Bhardwaj, Swati (British journal of nutrition, 2009)
A role of dietary nutrients in relation to insulin resistance has been suggested but conclusive evidence in human beings is lacking. Asian Indians and South Asians are prone to develop insulin resistance and the metabolic syndrome. In the present paper, data pertaining to nutrient intake, insulin resistance and cardiovascular risk factors in Asian Indians and South Asians have been reviewed. In these populations, several dietary imbalances have been reported: low intake of MUFA, n-3 PUFA and fibre, and high intake of fats, saturated fats, carbohydrates and trans-fatty acids (mostly related to the widespread use of Vanaspati, a hydrogenated oil). Some data suggest that these nutrient imbalances are associated with insulin resistance, dyslipidaemia and subclinical inflammation in South Asians. Specifically, in children and young individuals, a high intake of n-6 PUFA is correlated with fasting hyperinsulinaemia, and in adults, high-carbohydrate meal consumption was reported to cause hyperinsulinaemia, postprandial hyperglycaemia and hypertriacylglycerolaemia. Dietary supplementation with n-3 PUFA leads to an improved lipid profile but not insulin sensitivity. Inadequate maternal nutrition in pregnancy, low birth weight and childhood ‘catch-up’ obesity may be important for the development of the metabolic syndrome and diabetes. Even in rural populations, who usually consume traditional frugal diets, there is an increasing prevalence of cardiovascular risk factors and the metabolic syndrome due to changes in diets and lifestyle. Nationwide community intervention programmes aimed at creating awareness about the consequences of unhealthy food choices and replacing them by healthy food choices are urgently needed in urban and rural populations in India, other countries in South Asia and in migrant South Asians.